PENGARUH KOMPETENSI SDM TERHADAP KUALITAS PELAYANAN PUBLIK DI RUMAH SAKIT UMUM DAERAH ADE MOHAMMAD DJOEN SINTANG - Maya Cynthia Rebecca E.42008029 (FISIP Universitas Tanjungpura Pontianak, 2012)
The title of this reseacrh is “ The Effect of Human Resource Competencies to The Quality of Public Services atAde M.Djoen General Hospital Sintang “. The reseacrh aims to find out how much the effect of human resourcecompetencies to the quality of public services at Ade M.Djoen General Hospital Sintang. The title based of issuesrelating to the implementation of health care at the hospital in order that the author assume that human resourcecompetencies is one of factor that influens to that problems. The research use quantitative methods with causalform. The research begins by performing the initial observation and the submission of proposal for research, thencreate and test validity and reliability question form. After that question form distributed to respondents andanalyzed in research report (essay). The respondents are civil servants of 7 units at the hospital. Based of statisticdata analysis, the competence of human resources have an effect to the quality of public service with significancelevel 26,1 % and the remaining 73.9% is influenced by other factors not examined as complete infrastructure,service mechanisms, management and finance.Keywords : competence and quality of public service